Study of Phytoconstituents and Biological Activities of Medicinal Plants of Chitwan District - Pokharel, Rama; Kalauni, Surya Kant (BMC Journal of Scientific Research, 2020)
Four plants species, namely; Calotropis gigantea, Ageratum houstonianum, Catharanthus roseus, Thevetia peruviana (seed), and Thevetia peruviana (leaves) have been collected from Chitwan, and the crude methanol extract of respective plants parts and seeds were studied for their phytoconstituents and biological activity. Phytochemical screening showed the presence of glycosides, flavonol glycosides and coumarin glycosides as rich components. The Brine-shrimp bioassay of various plants extract showed that C. gigantean, A. houstonianum and C. roseus exhibited high toxicity against brine shrimp nauplii at LC50 (μg/ml) values of 23.44, 27.54 and 83.17 respectively. In addition to this, study of antimicrobial activity of respective plants extract on methanol showed that, all the four plants species were highly active for Staphylococcus aures and C. gigantea is pharmacologically active for other bacteria such E. coli, S. aures, K. oxytoca and P. aeruginosa. Study of anti-cancer activity on human pancreatic cancer cells such as PANC-1 revealed that the preferential cytotoxic activity of crude methanol extract of C. gigantea was highest at 100μg/ml for both NDM and DMEM.